PENGETAHUAN SUAMI DAN KETERLIBATANNYA DALAM PERAWATAN KEHAMILAN ISTRI DI DESA RANAH SINGKUANG KECAMATAN KAMPAR KABUPATEN KAMPAR - Gusti Randa; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The background of this research come from the autor’s observation of husband’s involvement in the pregnancy of the wife in the village of Ranah Singkuang. The formulation of the problem in this study is how modern knowledge and traditional knowledge of husbands about pregnancy and how the husband’s involvelment in the care of the wife’s pregnancy in the village of Ranah Singkuang. The purpose of this study was to determine the husband’s modern and tradisional knowledge about pregnancy and to find out the husband’s involvement in the wife’s pregnancy. This study uses descriptive qualitative research methods. The population in this study was a husband whose wife was pregnant or the age of his last child was a maximum of 2 year. The sample in this study amounted to 48 people. Determination of samples using totally population technique. The result of the study showed that the most modern level of husband’s husband was in the moderate category with a total of 47.9% , and the level of tradisional knowledge wasat most in the low category with a total of 41,7%, and the involvemet of husbands in the care of the wife’s pregnancy,the involvement of the husbands was the motivator with the most categories in the high category with a total of 54.2%, most fasilitators are in the high category with a total of 45.8%, and most involvement as an educator is in the high category with a total of 79.2%.The conclusion of this study is that the husband’s moderen knowlwdge is the relatively high whil his tradisioanal knowledge is still low, wil the level of involvement is also high.Keywords: Knowledge, Involvement, husband, wife, Pregnancy